2=7(6+10f)

Simple and best practice solution for 2=7(6+10f) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2=7(6+10f) equation:



2=7(6+10f)
We move all terms to the left:
2-(7(6+10f))=0
We add all the numbers together, and all the variables
-(7(10f+6))+2=0
We calculate terms in parentheses: -(7(10f+6)), so:
7(10f+6)
We multiply parentheses
70f+42
Back to the equation:
-(70f+42)
We get rid of parentheses
-70f-42+2=0
We add all the numbers together, and all the variables
-70f-40=0
We move all terms containing f to the left, all other terms to the right
-70f=40
f=40/-70
f=-4/7

See similar equations:

| x+69+21=180 | | 2(t–2)+-3=13 | | 7/2x-1/2=55/2 | | 6+7n=27 | | z-15/4=1 | | 3/x=-1.5/15 | | 5x-12=-5(-x+13) | | 1/3(24x+6)-6=-44 | | 7x+4=12x-2 | | 9(b+2)=5-(-9b-13) | | 2x-5(x-5)=-2+5x-21 | | 5x+9=72 | | 15=2y/3+6 | | 5x=8=899 | | x-3=4÷x-3 | | t2+8t+15=0 | | 0=7u-7u | | 9+3(x-9)=8-5(x-9) | | (154+198+x)/3=160 | | 154+198+x=160 | | 2(c-3)+4=10 | | -2(x+5)=4(3x+8) | | 2(c–3)+4=10 | | 88-(3c+4)=2(c+5)+c | | 8x-5x+170=8x+75 | | 12/x+2+26/2x+1=5 | | 1-g=-8 | | 1–g=-8 | | 12-4x+x=-3 | | 3x+15+60+90=180 | | (12/x-2)+(26/2x+1)=5 | | 8+2x−4=6+2(x−1) |

Equations solver categories